Unraveling the impact of urban landscape pattern changes on habitat quality: a case study of Jinan City in the lower Yellow River Basin, China - Tongwen Liu; Guangting Yu; Sijia Yan; Jinda Xu; Liming Xue; Guanhan Song; Qi Wang (Ecological Indicators)
The changes in landscape patterns induced by human activities such as the urban expansion and resource exploitation during the process of urbanization significantly affects habitat quality. However, there are insufficient studies on the spatial heterogeneity of landscape pattern changes and habitat quality and their spatio-temporal influencing mechanism, which hampers the optimization of regional land spatial layout and the formulation of ecological protection policies. Therefore, an analytical framework coupling the InVEST model, Geodetector and spatial statistical model was proposed in this study. Then, the impact mechanisms of landscape pattern changes on habitat quality and its spatial spillover effects were explored in Jinan, a typical city in the lower reaches of the Yellow River Basin, for the years 2000, 2010 and 2020. The results indicate that over the 20-year period, Jinan experienced high dynamic changes in land use and land cover (LULC), leading to an increasingly fragmented landscape. Consequently, the spatial heterogeneity of habitat quality has been progressively enhanced, exhibiting an unbalanced spatial distribution with higher values in the south and lower values in the north. However, the gap between improvement and degradation ratios has narrowed by threefold over the 20 years. Expansion of mining land, fragmentation of woodland landscapes, and decrease in patch diversity were identified as the dominant factors causing the decline in habitat quality, while the restoration of water bodies and woodland landscapes, along with the recovery of patch diversity were the core reasons for promoting habitat quality improvement. Additionally, the spatial spillover range of landscape pattern changes on habitat quality improvement and degradation is similar (about 1200 m), but the spatial spillover intensity of degradation is significantly stronger than that of improvement, about twice as much. This study can provide a scientific support for urban spatial structure planning, ecological resource deployment and ecological restoration efforts.